ECONOMIC INNOVATIONS OF THE PAST ERA - A. Chernikov (Управленческие науки, 2016)
The article considers the methods of organizing, planning and managing the production which were innovative in different periods of Soviet economic management system. Practically all of them are considered to be the basis for modern innovative management methods.Reduced expenditures method appeared in the USSR in the industrialization period for the large-scale projects’ efficiency assessment. It’s applied even nowadays while comparing different capital investmentswhich have equal results.The organization of project-constructive works and productions (as a method of minimizing the new manufactures’ introduction terms) was used in pre-war years and then in 1960s in space industry.A system of defectless production manufacture (1955) has become the basis for different systems of managing the production quality which are considered to be the prototypes of today KPI, and the communist labour movement (1958) brought up the labour person and encouraged him to be aware of morale stimuli. The functional and price analysis, as a method of reducing the costs, was practically implemented in 1970s.Then in the late 1970s and during the early 1980s the experiments on the implementation the system of planning and accounting the national economic effect in production capacity dynamics under the influence of scientific and technical progress, including the concept of indicators’ balanced system were held.The collective forms of labour organization and incentive in large subdivisions were firstly applied as early as 1930s in the industrialization period and were developed during the early 1990s. Today it’s mainly reflectedin KPI.Special-purpose programme of planning in the branches of industry (1980s) is actually used today in managing public and municipal finances.Acting since the second half of the 1980s the different models of self-accounting have been reflected incollective forms of real-estate and leasing relationships.The article describes the main content of methods, analyses the causes of their non-spreading in order to study the possibilities of their application under the modern conditions.